The Factors of Needlestick Injury on Healthcare Workers at the Hospital of Bojonegoro - Anisa Fitria; Deviyanti Wahyu Izati; Tri Martiana (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Needlestick injury is the most frequent accidents encountered by healthcare workers in the hospital. Needlestick injury can expose healthcare workers to the risk of communicable diseases infection. This study was conducted in one of the hospitals in Bojonegoro. Healthcare workers in the inpatient installation and laboratory room have a potential for needlestick injury since they often use needles in their work activities. The aim of this study was to analyze the needlestick injury-related factors on healthcare workers in one of the hospitals in Bojonegoro. Methods: This study belongs to a cross-sectional study with a quantitative approach. The study population comprised all laboratory staffs and nurses in the inpatient installation. Sampling was done using stratified random method, obtaining 91 people as the samples. The variables involved in this study included educational level, knowledge, training, unsafe action, and needlestick injury. Data were acquired by means of observation, questionnaire, hospital data, and other supporting data. The data obtained were analyzed using the chi square test with a significance of 0.05 (α = 0.05). Result: This study indicates that educational level (sig = 0.024) and unsafe action (sig = 0.002) are related to needlestick injury. Meanwhile, knowledge (sig = 0.722) and training (sig = 0.350) are not related to needle stick injury. Conclusion: Educational level and unsafe actions are related to needlestick injury on healthcare workers at one of the hospitals in Bojonegoro.Keywords: accident, hospital, needlestick